The Empirical Interpretation of French Cartesianism: The Académie des Sciences, the Journal des Sçavans and the Relationship with the Royal Society - Nausicaa E. Milani (Noctua, 2014)
The Système de philosophie (1691) by Pierre Sylvain Régis can be considered as the achievement both of the scientific liveliness of the Académie des Sciences in the 17th century and of its fruitful relationship with the Royal Society. Since it aims to shape the new conception of the universe in terms of a system, the Système represents one of the most mature achievements of Cartesian philosophy and it is characterized by an empirical interpretation of Descartes’ thought. The Système therefore reflects two important phenomena occurring in the Europe of the 17th century: the scientific revolution and the proliferation of Academies. In fact, this ambitious work could be undertaken with the support of the Académie des Sciences and the Journal des Sçavants. My paper will analyse the French context by focusing to outline the role which the Académie de France had both in France, as the medium of dissemination of the new philosophy despite censorship, and abroad, in particular through the relationship with the Royal Society in England. I aim to analyse the role of the Journal des Sçavants as a means to share ideas other than by correspondence and as a trait d’union between “rationalist France” and “empiricist England”. I intend to question whether it is possible to establish a connection between the empirical interpretation of French Cartesianism, the consolidation of the Académie de France and the employment of new means of academic communication. The paper will show that the second half of 17th century France represents a remarkable exception to the conventional picture, which states that in 17th century Europe, following the success of a mechanistic interpretation of reality, two philosophical school clashed: rationalism, predominating on the continent, and empiricism, in England.